Analysis the Learning Activities which included in the Social Studies books for the First Four grades of the Basic Education Stage in Light of the Values of Citizenship (Journal of Hama University, 2021)
This research aims to know the degree of citizenship values availability in the content of the activites of social studies books for the first four grades of the basic education stage and the degree of focus on it. The researcher selected an intentional sample that cover every educational activity include the subject of the research in the social studies books. Due to the nature of the research and the goals which it seeks to achieve, the researcher used the descriptive analytical approach, by content analysis method.A list of the most important major and minor citizenship values was prepared by (28) sub-values which are distributed in five main values (belonging to the homeland, a wareness of rights, commitment to duties, forgiveness, participation). After verifying the validity and reliability of the tool, the books were analyzed and the analysis process led to the following results; the values of citizenship as a whole got high percentages from all activities of each book despite of the different sub-values percentages, there was a kind graduation in its percentages as a whole, it reached 43% in the first grade and increased in the second grade to reach 51% then it got 56% in the third grade and 57% in the fourth grade.As for the degree of focusing on it, the citizenship values occupied a large share of the course activities content, as the number of pages which occupied by the main citizenship values reached 45% out of all the pages of the first grade book and it increased to 49% from the entire pages of second grade books, but in the third grade books it reached 59% and it maintained this increasing to reach 61% in the fourth grade. Although the percentages are not equal, but they are close and gradual despite of different sub-ration. The research concluded to set of recommendations and proposal that it is hoped to implement and take into account.